The Oxford Dodo. Seeing more than ever before: X-ray micro-CT scanning, specimen acquisition and provenance. (3rd October 2021) - Warnett, J. M.; Williams, Mark A.; Wilson, Paul F.; Smith, M. Paul
ABSTRACT: The Oxford Dodo ( Raphus cucullatus ) has been in the collections of the University of Oxford since 1683, first in the Ashmolean Museum and latterly in Oxford University Museum of Natural History. Prior to this the specimen was part of the collections of the Tradescants, father and son, and likely acquired between 1634 and 1656, in the Musæum Tradescantianum in what is now Vauxhall, south London. It has been thought probable that this specimen was once the live bird recorded in London by Sir Hamon L'Estrange in around 1638, but X-ray CT scanning of the skull for anatomical investigation has cast doubt on the provenance of the Oxford Dodo. The 3D visualisation revealed 115 metal particles embedded within the bone of the skull, concentrated in the left side of the skull. All but five of the particles are less than 1 mm in diameter and their location leads to the conclusion that they represent lead shot consistent with the bird being shot from the rear right of the head, perhaps with a ventral component. This forensic discovery leaves the provenance of the Oxford specimen uncertain but illustrates the value of non-invasive visualisation techniques in determining the potentially complex histories of unique museum objects. GRAPHICAL ABSTRACT: uf0001